(untitled) (Globalization and Business, 2023)
The COVID-19 pandemic has led us to the need of choosing between short-term and long-term priorities. In order to conduct and evaluate effective policies, new types of models are required, that are able to incorporate both epidemiological and economic variables. The aim of this paper is to make practical use of theoretical framework in case of Georgia and lay the foundation for future research. The theoretical framework of the paper is based on the macroeconomically extended version of epidemiological SIR type model developed by Eichenbaum et al. (Eichenbaum, Rebelo, Trabandt, 2020). In the homogenous economic agent model human behavior determines the epidemiological situation in the country. Individuals are reducing the probability of infecting themselves by reducing consumption and labor supply. However, consumers do not take into account the possibility of them infecting others, thus creating the negative external effect. Therefore, these effects can be internalized using the containment policy, which is represented as tax on consumption in the model. By raising taxes, the government increases the relative price of consumption to leisure (the economic agent chooses what part of one’s time to devote to the labor market and what part of time to devote to leisure). Consequently, on other equal terms, households will change their behavior and prefer to stay at home, which is their response to the increased tax. However, these actions have a big impact on output. An epidemic ends when a large part of the population acquires collective immunity. In the absence of a vaccine and effective treatment, immunity can be generated by transmission of the virus and subsequent recovery. At this time, the number of deaths due to the virus is increasing. In this model, it is optimal to gradually increase the containment measures in parallel with the increase in virus cases, and to gradually mitigate the measures as the community approaches the critical level of immunity. This will help increase the share of people with immunity and, in the event of a high level of infection, deter infected people. The paper uses the mentioned theoretical framework in practice, taking into account the epidemiological and economic state in Georgia and investigates the short and long run effects of the pandemic on population health, as well as their economic behavior. In the short run the containment policy leads to deep recession, although it reduces the number of infected and deceased. Therefore, in this case there is a choice to be made between epidemiological and economic situations in the short run. However, in the long run, the negative impact of the pandemic on the economy is weaker when using the containment policy, than in case of not using it at all.